Continuous liquid interface production of 3D printed drug-loaded spacers to improve prostate cancer brachytherapy treatment. (August 2022) - Hagan, C. Tilden; Bloomquist, Cameron; Kim, Isaiah; Knape, Nicole M.; Byrne, James D.; Tu, Litao; Wagner, Kyle; Mecham, Sue; DeSimone, Joseph; Wang, Andrew Z.
Abstract: Brachytherapy, which is the placement of radioactive seeds directly into tissue such as the prostate, is an important curative treatment for prostate cancer. By delivering a high dose of radiation from within the prostate gland, brachytherapy is an effective method of killing prostate cancer cells while limiting radiation dose to normal tissue. The main shortcomings of this treatment are: less efficacy against high grade tumor cells, acute urinary retention, and sub-acute urinary frequency and urgency. One strategy to improve brachytherapy is to incorporate therapeutics into brachytherapy. Drugs, such as docetaxel, can improve therapeutic efficacy, and dexamethasone is known to decrease urinary side effects. However, both therapeutics have high systemic side effects. To overcome this challenge, we hypothesized that we can incorporate therapeutics into the inert polymer spacers that are used to correctly space brachytherapy seeds during brachytherapy to enable local drug delivery. To accomplish this, we engineered 3D printed drug-loaded brachytherapy spacers using continuous liquid interface production (CLIP) with different surface patterns to control drug release. These devices have the same physical size as existing spacers, allowing them to easily replace commercial spacers. We examined these drug-loaded spacers using docetaxel and dexamethasone as model drugs in a murine model of prostate cancer. We found that drug-loaded spacers led to higher therapeutic efficacy for brachytherapy, and there was no discernable systemic toxicity from the drug-loaded spacers. Statement of significance: There has been high interest in the application of 3D printing to engineer novel medical devices. However, such efforts have been limited by the lack of technologies that can fabricate devices suitable for real world medical applications. In this study, we demonstrate a unique application for 3D printing to enhance brachytherapy for cancer treatment. We engineered drug-loaded brachytherapy spacers that can be fabricated using Continuous Liquid Interface Production (CLIP) 3D printing, allowing tunable printing of drug-loaded devices, and implanted intraoperatively with brachytherapy seeds. In combined chemotherapy and brachytherapy we are able to achieve greater therapeutic efficacy through local drug delivery and without systemic toxicities. We believe our work will facilitate further investigation in medical applications of 3D printing. Graphical abstract: Image, graphical abstract